PHILIPPE DE VITRY, BISHOP OF MEAUX. (October 2019) - Wathey, Andrew
Abstract: Philippe de Vitry's tenure of the bishopric of Meaux in the last decade of his life, 1351–61, the crowning event of his court and church career, has often been regarded as a period of retirement from creative activity. A reassessment of this judgement is timely, following new musical discoveries and literary work exposing links between Vitry and his contemporaries. Using new archival material, this article explores the geopolitical context of Vitry's work in the diocese of Meaux; his engagement with political society, king and court; and his role in events under a national government fractured by the capture of Jean II at Poitiers in 1356. It examines the interplay of Vitry's career, relationships and output, identifying the composer's house in Paris, and exploring his family relationships, and his engagement with Pierre Bersuire, among others, in the creative circles of mid-fourteenth-century Paris. It also illuminates a context and opportunities for the continuation of his creative work into the late 1350s, some remnants of which survive in the literary miscellany Paris, BN Lat. 3343.